A Herbal Mixture Formula of OCD20015-V009 Prophylactic Administration to Enhance Interferon-Mediated Antiviral Activity Against Influenza A Virus - Kwon, Eun-Bin; Oh, You-Chang; Hwang, Youn-Hwan; Li, Wei; Park, Seok-Man; Kong, Ryong; Kim, Young Soo; Choi, Jang-Gi (Frontiers in Pharmacology, 2021)
OCD20015-V009 is an herbal mix of water-extracted Ginseng Radix, Poria (Hoelen), Rehmanniae Radix, Adenophorae Radix, Platycodi Radix, Crataegii Fructus, and Astragali Radix. In this study, its in vitro and in vivo antiviral activity and mechanisms against the influenza A virus were evaluated using a GFP-tagged influenza A virus (A/PR/8/34-GFP) to infect murine macrophages. We found that OCD20015-V009 pre-treatment substantially reduced A/PR/8/34-GFP replication. Also, OCD20015-V009 pre-treatment increased the phosphorylation of type-I IFN-related proteins TBK-1 and STAT1 and the secretion of pro-inflammatory cytokines TNF-α and IL-6 by murine macrophages. Moreover, OCD20015-V009 prophylactic administration increased IFN-stimulated genes-related 15, 20, and 56 and IFN-β mRNA in vitro. Thus, OCD20015-V009 likely modulates murine innate immune response via macrophages. This finding is potentially useful for developing prophylactics or therapeutics against the influenza A virus. Furthermore, pre-treatment with OCD20015-V009 decreased the mortality of the mice exposed to A/PR/8/34-GFP by 20% compared to that in the untreated animals. Thus, OCD20015-V009 stimulates the antiviral response in murine macrophages and mice to viral infections. Additionally, we identified chlorogenic acid and ginsenoside Rd as the antiviral components in OCD20015-V009. Further investigations are needed to elucidate the protective effects of active components of OCD20015-V009 against influenza A viruses.